Comunidades terapêuticas : "novas" perspectivas e propostas higienistas - Ramos, Renata Cristina Marques Bolonheis (2012)
Lately, we have observed a retaking of the discussions on the use of alcohol and other drugs, not only in Brazil, but in several countries of the world. In fact, nowadays the subject represents a great problem, which has been sensitizing the public opinion and calling the attention of the media, being a lot of times treated in a superficial way, with lots of prejudice. With that, the democratic debate is made unfeasible and the problem is deviated from its context and socio-historical development. In this sense, we want to say that the use of psychoactive substances is not a subject of the present time, as we can see for instance, the mobilization of the hygienists along with the Brazilian League of Mental Hygiene (LBHM) in the beginning of the XX century. Many were the investments and the campaigns of that entity against alcoholism in the Brazilian society. Thus, the present study has the objective to highlight the relationship between the presuppositions defended by the hygienists in the first half of the XX century concerning the use of psychoactive substances, the current public politics on alcohol and other drugs in Brazil, and the proposals of intervention of the therapeutic communities (CT) at the present time. We focused our study in such entities, because the same ones which, until the year of 2010 were not under the Basic Health System (SUS) were then included in the net of psychosocial attention what has caused controversies and discussions on the part of entities and categories interested in the subject. To reach the proposed objective, we accomplished a bibliographical and documental research approaching the subject alcohol and other drugs, since the beginning of the century up to the current discussions, with focus in the therapeutic communities. In the development of this study readings and inspired analyses were accomplished following the historical materialism. It was possible to identify approaches on the treatment proposed by the hygienists and by the therapeutic communities of the present time. As a conclusion, we can say that almost a century has passed since the hygienists began their march against alcohol, and the problem seems worse. Different forces, interests, needs, of political, economic and social scope, are weaving the complex history of the attention to the users of alcohol and other drugs. And if the problems are produced by the society, it is of that group that the solution should come, even though the history tells that the major charges have been attributed to users, to the people they live with, and to the public health.